2020
DOI: 10.3390/ma13112644
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Study of Shear Bond Strength in Direct and Indirect Bonding with Three Types of Adhesive Systems

Abstract: This study aimed to compare the shear bond strength (SBS) and adhesive remaining index (ARI) using one conventional and two novel adhesive systems with clinical step reduction and direct and indirect bonding. A sample of 72 human premolars were divided into six groups of 12 samples. The first three groups (G1, G2, G3) were bonded with a direct technique, while the remaining groups (G4, G5, G6) were bonded by the indirect technique. Groups G1 and G4 used conventional acid-etching primer composite (XT); groups G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 45 publications
2
7
0
3
Order By: Relevance
“…Many studies have analyzed the enamel characteristics after bracket debonding concerning enamel loss, roughness, shear bond strength, and adhesive remnant index [ 18 , 19 ]. However, no other study was found by the investigators with regard to these same parameters in lingual retentions.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have analyzed the enamel characteristics after bracket debonding concerning enamel loss, roughness, shear bond strength, and adhesive remnant index [ 18 , 19 ]. However, no other study was found by the investigators with regard to these same parameters in lingual retentions.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has focused on reducing the number of bracket attachment process while increasing its durability ( Latta and Radniecki, 2020 ). For example, self-adhesive resin (SAR) is a product that does not use an adhesive, and because it reduces the bracket attachment process by one-step, it can help to reduce the overall level of adhesive residue ( Cengiz and Ünal, 2019 ; Iglesias et al, 2020 ; Rasmussen et al, 2020 ; Ok et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Na ortodontia, os sistema de adesivo ideal é aquele que, apresenta retenção suficiente para suportar esforços da mastigação e de forças geradas pela mecânica ortodôntica, (CERONE et al, 2019) permitindo o posicionamento preciso dos acessórios e remoção dos mesmos sem danificar o esmalte dentário (IGLESIAS et al, 2020;KACHOEI et al, 2016) contudo, na colagem dos acessórios ortodônticos, uma força de adesão muito alta nem sempre é favorável, pois poderia danificar a superfície de esmalte no momento da descolagem (DELAVARIAN et al, 2019;NASEH et al, 2018).…”
Section: Introductionunclassified